Proyecto de Factibilidad para la Implementación de una Empresa de Confección y Comercialización de Ropa para Mascotas Caninas de Raza Pequeña, en la Ciudad de Piñas, Provincia de El Oro - Loja Matailo, Luz Rebeca (2016)
This project has been carried out, in order to determine the feasibility of creating a company dedicated to the manufacture and marketing of clothing for small breed canine pets in the of Piñas city. This project aims to make and sell pet clothing small breed using innovative technology, occupying the local workforce, with resources of the area for products that can go to market in optimum condition, quality and price. This work corresponds to a feasibility study designed to determine the advisability of implementing a company that provides this service. The methodology used throughout this project use the following methods such as: inductive, deductive and analytical method; and the following technique as the survey. The project includes market research, in which the conditions of demand and supply are determined, the same as estimated a total of $ 7,876 unmet demand and finally a marketing plan. Then the technical study that has an installed capacity of 26,280 garments per year capacity, and capacity utilization of 3 items per hour giving us a total of 6,264 garments a year working 261 days analyzed; location, project engineering and organizational structure, the same legally established as a Limited Unipersonal company with the name "CLOTHES IAN", Cia. Unipersonal Ltda. As regards the financial study different budgets was determined and thus determine the amount of investment $ 4.899,09 and its financing, the same as a credit of 41% of the total investment will ask the Bank national Development and the other 59% of the investment will be obtained from the Business Partners also has a total production cost for the first year of $ 26,956.58; unit cost of each garment in the first year is $ 4.30; 5 plus net profit to be obtained in the first year of operation is $ 4468.05 while liquid will in profit in the amount of $ 4,021.25; and finally the financial evaluation was conducted to determine the feasibility of the project through the following indicators as Net Present Value (NPV) of $ 12,415, Internal Rate of Return (IRR) of 96.52%; in the benefit cost $ 0.25 cents for every dollar invested; within the Recovery Period Capital investment is recovered in 11meses with 9 days, Sensitivity Analysis costs may be increased by 15% and a decrease in revenue of 12% supporting the project. Finally the conclusions and recommendations made; the literature was the source of consultation and support to break down and understand the project and reach completion, the project also collecting Annexes on components of the thesis project was supplemented.